2011
DOI: 10.1021/pr200102h
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometric Assay for Analysis of Haptoglobin Fucosylation in Pancreatic Cancer

Abstract: A mass spectrometric method was developed to elucidate the N-glycan structures of serum glycoproteins and utilize fucosylated glycans as potential markers for pancreatic cancer. This assay was applied to haptoglobin in human serum where N-glycans derived from the serum of 16 pancreatic cancer patients were compared with those from 15 individuals with benign conditions (5 normals, 5 chronic pancreatitis, and 5 type II diabetes). This assay used only 10uL of serum where haptoglobin was extracted using a monoclon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
87
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(92 citation statements)
references
References 31 publications
(62 reference statements)
4
87
1
Order By: Relevance
“…Recent studies have reported that serum CA19-9 levels can detect pancreatic cancer independently (35) or as a component of a multiple marker panel (36), although other reports have concluded that it is not specific for the diagnosis of cancer (12,37). In addition to CA19-9, increases in core fucosylation of serum proteins such as ribonuclease 1 (38) and both core and outer arm fucosylation of haptoglobin (16,17) have been reported as putative biomarkers. A considerable amount of research has been conducted to investigate glycan biomarkers as a potential molecular marker system for pancreatic cancer; however, very little information is available with regard to the variety and abundance of glycans (or glycoproteins) that are present in the tissues and fluids of the pancreas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have reported that serum CA19-9 levels can detect pancreatic cancer independently (35) or as a component of a multiple marker panel (36), although other reports have concluded that it is not specific for the diagnosis of cancer (12,37). In addition to CA19-9, increases in core fucosylation of serum proteins such as ribonuclease 1 (38) and both core and outer arm fucosylation of haptoglobin (16,17) have been reported as putative biomarkers. A considerable amount of research has been conducted to investigate glycan biomarkers as a potential molecular marker system for pancreatic cancer; however, very little information is available with regard to the variety and abundance of glycans (or glycoproteins) that are present in the tissues and fluids of the pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…A subgroup of the cysts, including several IPMN, was observed here to contain hyperfucosylated N-linked glycans. Increased fucosylation has continued to be implicated in the progression of cancer (13)(14)(15)(16), including specifically pancreatic cancer (16,17). As such, hyperfucosylated N-glycans and glycoproteins have been targeted for quantitative label-free bottom-up glycoproteomic analysis.…”
mentioning
confidence: 99%
“…The results of the present study provide evidence that the N-glycan on GLUT4 not only plays a general role in protein stability, but also has a function in GLUT4 sorting and insulin responsiveness. It should be noted that several studies have demonstrated changes of N-glycan profiles under diabetic conditions (43)(44)(45)(46), and the effects of glycan profile alterations, especially in GLUT4, on the insulin resistance phenotype in type 2 diabetes should therefore be carefully investigated in future studies. Clarification of the key factors involved in N-glycan-related intracellular trafficking will be imperative for understanding the precise roles of the N-glycan functions in GLUT4.…”
Section: Discussionmentioning
confidence: 99%
“…The authors also detected traces of doubly fucosylated Le(y)-type structures in tetra-antennary glycans. Lin et al (42) reported increased core fucosylation in patients with pancreatic cancer; both core and outer arm fucoses were detected among the doubly fucosylated glycans. Dimeric Lewis-A type (Le(a) on Le(a)) structures of Hp were found increased in colon cancer (43).…”
Section: Glycosylation Of Hp In Cancer Andmentioning
confidence: 99%